LEGIS INDEPENDENCE RATIO OF JUDICIAL POWER IN THE CRIME OF CORRUPTION IN COMPARATIVE INDONESIA WITH HONG KONG - Ahmad Fauzi; M. Noor Fajar; Deni Achmad (PRANATA HUKUM, 2023)
In a country the distribution of power based on trias politica will place state power in the executive, legislative and judicial branches. With regard to judicial power, the court institution in carrying out its functions is provided by the principle of independence of judicial power, this principle is the main principle for the court in protecting human rights, the rule of law and also justice. The principle of the independence of judicial power in its application, the judge in carrying out his duties must carry out the judicial function in accordance with the oath and the law without any interference from any party (directive). In the Indonesian legal system, judicial power is regulated in the provisions of Article 24 paragraph (2) of the 1945 Constitution which states that judicial power is exercised by a Supreme Court and judicial bodies under it within the general court environment, religious court environment, military court environment, administrative court environment. state and by a Constitutional Court. This research is a legal research with a legal comparison method between the Indonesian legal system and the Hong Kong legal system, where the analysis makes a country's national law more coherent when compared to other countries. The first result: the establishment of a corruption court in Indonesia is in line with the UNCAC convention and also the Declaration of Human Rights, in which the formation of a corruption court in Indonesia uses a court structure and ad hoc judges which have many weaknesses in the aspect of guaranteeing the independence of judicial power for ad hoc judges . Second: the formation of a corruption court in Hong Kong is guaranteed in the constitution with regard to institutions and institutions, the Hong Kong constitution stipulates a prohibition on the establishment of an ad hoc court, therefore the corruption court in Hong Kong is a permanent court structure and not ad hoc in nature. So that the guarantee of the independence of the judiciary against judges is more guaranteed.